STUDY OF DR. BHIMRAO AMBEDKAR'S SOCIAL THOUGHTS: SOCIOLOGICAL STUDY - Arya, Mohan Lal; Trikoti, Sarita (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Baba Saheb wanted to develop a society in which there is an empire of equality, freedom and fraternity. Baba Saheb wanted to create social consciousness among the people but he considered social consciousness to be very important for social development and solution of social problems. According to Baba Saheb, social consciousness is the protector of the rights of the individual. The aim of the social struggle done by Dr. Bhimrao Ambedkar was to end the atrocities on the neglected class, but Baba Saheb wanted that all sections of the society should have equal place in all areas and people of all classes should be given equal opportunities to rise in life. For all these works, Dr. Bhimrao Ambedkar worked hard and diligently. In the research paper, it has been described that how Dr. Bhimrao Ambedkar tolerated untouchability and caste discrimination in the society and how he kept trying to solve this problem. In the presented research paper, the important changes made by Baba Saheb Dr. Bhimrao Ambedkar in the social field have been described.